ANALISIS PENGARUH KUALITAS LAYANAN DAN TARIF PREMI TERHADAP KEPUASAN NASABAH DAN SWITCHING INTENTION PADA PT.PRUDENTIAL LIFE ASSURANCE KOTA PEKANBARU - Febrina Harianja; Zulkarnain Zulkarnain; Henni Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research is conducted to analyze the influence of service quality and tariffs of premiums to customer satisfaction and switching intention on PT.Prudential Life Assurance Pekanbaru city.There are four latent variables in this research such as Service Quality (X1), Tariffs of Premiums (X2), Customer Satisfaction (Y1) Switching Intention (Y2). The population of this study are all customer who is still an active customer at PT. Prudential Life Assurance Pekanbaru until 2015 with a sample of 100 respondents were selected by using purposive sampling method with criteria is an active customer in Prudential Insurance, a customer who pays his / her insurance premium for a monthly or quarterly period and has been enrolled as an active customer for at least 1 year. Data are taken by giving respondents structural questionaires. Meanwhile, Path Analysis method are chosen for data analysis by SPSS version21.The result of this research shows that 1)Service Quality has a positive and significant effecttoward Customer Satisfaction,2)Tariffs of Premium has positive and significant effect toward Customer Satisfaction,3) Service Quality has negative and significant effect toward Switching Intention through Customer Satisfaction as Intervening , 4) Tariffs of Premium has negative and significant effect toward Switching Intention through Customer Satisfaction as Intervening, and 5) Customer Satisfaction has negative and significant effect toward Switching IntentonKeywords: Service Quality, Tariifs of premiums, Customer Satisfaction,and Switchimg Intention